Protocol for quantitative characterization of human retinotopic maps using quasiconformal mapping - Duyan Ta; Negar Jalili Mallak; Zhong-Lin Lu; Yalin Wang (STAR Protocols, 2023)
Summary: High-field functional magnetic resonance imaging generates in vivo retinotopic maps, but quantifying them remains challenging. Here, we present a pipeline based on conformal geometry and Teichmüller theory for the quantitative characterization of human retinotopic maps. We describe steps for cortical surface parameterization and surface-spline-based smoothing. We then detail Beltrami coefficient-based mapping, which provides a quantitative and re-constructible description of the retinotopic maps. This framework has been successfully used to analyze the Human Connectome Project’s V1 retinotopic maps.For complete details on the use and execution of this protocol, please refer to Ta et al. (2022).1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.